IMPLEMENTASI PROGRAM PENYIAPAN KEHIDUPAN BERKELUARGA BAGI REMAJA (PKBR) DI BADAN PEMBERDAYAAN PEREMPUAN KELUARGA BERENCANA (BPPKB) KABUPATEN BENGKULU TENGAH (Kajian Pada PIK-R SMAN 1 Talang Empat Kabupaten Bengkulu Tengah) - Febriani - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to describe the implementation of the Life Setup program for adolescentsconveyed throughYouth Information and Counseling Center at Senior High School 1 Talang Empat Central Bengkulu District.This research was a qualitative research. Informants in this study were selected by snowball sampling techniques, namelyWomen Empowerment Family Planning, Supervisor of Youth Information and Counseling Center, Counseling teachers and students and Senior High School 1Talang Empat. Data collection techniques in this study using observation, interview and documentation study.Data analysis technique used was descriptive analysis.From the results of this research noted that the implementation of the Life Setup program delivered through Youth Information and Counseling Center in Senior High School 1 Talang Empat Central Bengkulu District was not operating effectively. The problem was,the lackness of socialization held by Women Empowerment on Family Planning Program on Life Setup program for adolescentsand also very rarely held a promotion to the students about the activities of Youth Information and Counseling Center at Senior High School 1 Talang Empat Central Bengkulu District, lack of supervision carried out by the Family Planning Extension given the task to supervise every activity takes place,the response of students was very little because they were not interested and not convincedthat the program wasn’t be able to solve their problems, there’s still a juvenile delinquency such as smoking, skipping, issued clothes and drinking, as well as almost every year a student found out because she became pregnant out of wedlock.